Largest case series of giant gallstones ever reported, and review of the literature - Al Zoubi, Mohammad (Int J Surg Case Rep, 2020)
INTRODUCTION: Giant/large gallstones have high risk of complications, and technical difficulties during surgery. This case series is the largest ever reported. PRESENTATION OF CASES: Case 1: Female (44 years), with one year intermittent right upper quadrant colicky pain. Ultrasound: large gallstone (normal gallbladder). Elective laparoscopic cholecystectomy (LC): 6 × 4 × 3.3 cm gallstone. Case 2: Female (41 years), presented to emergency room with 3 days right upper quadrant pain/tenderness, vomiting, and positive murphy’s sign. Ultrasound: large gallstone, calculus cholecystitis. Emergency LC: 4.5 × 3.1 × 3.5 cm gallstone. Case 3: Male (38 years), with history of gallstones and acute cholecystitis presented with intermittent right upper quadrant pain (2 months) and vomiting. Normal abdominal examination. Ultrasound: large gallstone. Elective LC: 4.1 × 4 × 3.6 cm gallstone. CONCLUSIONS: Gallstones >5 cm are very rare, with higher risk of complications. Gallbladder should be removed even if asymptomatic. Gallstones >3 cm have increased risk for gallbladder cancer, biliary enteric fistula and ileus. LC has challenges that include grasping the gallbladder wall, exposure of Calot’s triangle, and retrieval of gallbladder out of the abdomen. LC appears to be procedure of choice and should be performed by an experienced surgeon, considering the possibility of conversion to open cholecystectomy in case of inability to expose the anatomy or intraoperative difficulties.